Development of scintillation detectors with light collection via wavelength shifting light guides for TAIGA experiment. Issue 1 (1st November 2022) - Kravchenko, E; Alizzi, J E; Astapov, I; Bezyazeekov, P; Borodin, A; Brueckner, M; Budnev, N; Chiavassa, A; Dyachok, A; Gafarov, A; Garmash, A; Grebenyuk, V; et al.
Abstract : The TAIGA gamma observatory is continuing its deployment at the Tunka valley, close to lake Baikal. The new, original detectors, able to work under severe conditions of Siberia, were developed to increase the TAIGA sensitivity for the study of gamma-quanta at energies about 1 PeV and above. The distinguishing feature of the detectors is the use of the wavelength shifting light guides for scintillation light collection on a photodetector. Several designs of the counters have been tested: equipped with PMT or SiPM photo-detectors, acrylic or polystyrene based scintillators with thickness from 1 to 5 cm and detecting area from 0.75 to 1.0 m 2 . The data on the amplitude of the signal from cosmic muons measured in different points within the counter are presented. The first 48 counters were produced and deployed in 2019 at the TAIGA experiment. They form 3 stations each with 8 surface detectors and 8 underground detectors buried at the depth of 1.7 m. After two winters, all counters are working.